2018
DOI: 10.1016/j.addbeh.2017.10.023
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a brief cessation induction intervention for waterpipe tobacco smoking: A pilot randomized clinical trial

Abstract: Background Waterpipe (WP) tobacco smoking delivers many of the same harmful toxicants as cigarette smoking and is on the rise in the US. This study evaluated the feasibility and initial efficacy of a brief personalized feedback intervention in affecting changes in WP smoking among current WP smokers. Methods Participants (N=109) were recruited as they entered WP lounges and completed a questionnaire and exhaled carbon monoxide (eCO) testing before entering the WP lounge. Participants were cluster-randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
2
11
1
Order By: Relevance
“…Similar to the present findings, another study reported a two-fold rate of cessation in the intervention group compared with the control [ 53 ]. Contrary to the present findings, no statistically significant difference was found in some other investigations between the intervention and control groups regarding the rate of hookah cessation [ 54 , 55 ]. This divergence can be partly due to the type of training intervention, duration of intervention, sample size, and characteristics of the target population.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to the present findings, another study reported a two-fold rate of cessation in the intervention group compared with the control [ 53 ]. Contrary to the present findings, no statistically significant difference was found in some other investigations between the intervention and control groups regarding the rate of hookah cessation [ 54 , 55 ]. This divergence can be partly due to the type of training intervention, duration of intervention, sample size, and characteristics of the target population.…”
Section: Discussioncontrasting
confidence: 99%
“…Epidemiological studies have shown that WP smoking is associated with increased risks of cardiovascular diseases,6 cancer (lung, oesophageal, head and neck, and gastric),7ā€“10 metabolic syndrome11 and chronic obstructive pulmonary disease (COPD) 12. An additional health risk that is of particular concern for young adults is nicotine dependence, and similar to any other tobacco product is represented in WP smokers by substance addiction behaviours 13ā€“19. In agreement with the health risks identified to date, analytical examination of the components in WP smoke include a mixture of chemicals with known or suspected disease-causative agents that closely resemble those found in cigarette smoke (CS), and in many cases at higher concentrations 20 21.…”
Section: Introductionmentioning
confidence: 83%
“…Two of the three trials in a recent Cochrane review reported on the effect of individual behavioural supportā€”one found it to be effective . Two other small RCTsā€”not eligible for inclusion in the above reviewā€”did not show any statistically significant effect of behavioural support in waterpipe smokers . We also observed fewer gastrointestinal symptoms in the varenicline arm than the previous trials.…”
Section: Discussionmentioning
confidence: 42%